Fetal and early postnatal lead exposure measured in teeth associates with infant gut microbiota. (November 2020) - Sitarik, Alexandra R.; Arora, Manish; Austin, Christine; Bielak, Lawrence F.; Eggers, Shoshannah; Johnson, Christine C.; Lynch, Susan V.; Kyun Park, Sung; Hank Wu, Kuan-Han; Yong, Germaine J.M.; Cassidy-Bushrow, Andrea E.
Highlights: We examined associations of Pb (measured in baby teeth) and infant gut microbiota. Pb was measured before and after birth; stool was collected at 1- and 6-months. Fetal Pb associated with 1-month Candida, Aspergillus, Malassezia, and Saccharomyces . Pb did not associate with overall structure of infant gut bacterial communities. Yet, some bacteria (e.g., Collinsella, Bilophila, Bacteroides ) associated with Pb. Abstract: Background: Lead (Pb) is an environmentally ubiquitous heavy metal associated with a wide range of adverse health effects in children. Both lead exposure and the early life microbiome— which plays a critical role in human development—have been linked to similar health outcomes, but it is unclear if the adverse effects of lead are partially driven by early life gut microbiota dysbiosis. The objective of this study was to examine the association between in utero and postnatal lead levels (measured in deciduous baby teeth) and early life bacterial and fungal gut microbiota in the first year of life. Methods: Data from the Wayne County Health, Environment, Allergy and Asthma Longitudinal Study (WHEALS) birth cohort were analyzed. Tooth lead levels during the 2nd and 3rd trimesters and postnatally (<1 year of age) were quantified using high-resolution microspatial mapping of dentin growth rings. Early life microbiota were measured in stool samples collected at approximately 1 and 6 months of age, using both 16S rRNA (bacterial) and ITS2 (fungal) sequencing. Of the 1, 258 maternal-child pairs in WHEALS, 146 had data on both tooth metals and early life microbiome. Results: In utero tooth lead levels were significantly associated with gut fungal community composition at 1-month of age, where higher levels of 2nd trimester tooth lead was associated with lower abundances of Candida and Aspergillus and higher abundances of Malassezia and Saccharomyces ; 3rd trimester lead was also associated with lower abundances of Candida . Though lead did not significantly associate with the overall structure of the infant gut bacterial community, it associated with the abundance of some specific bacterial taxa, including the increased abundance of Collinsella and Bilophila and a decreased abundance of Bacteroides taxa. Conclusions: The observed associations between lead exposure and infant gut microbiota could play a role in the impact of lead on childhood development. Given the paucity of research examining these associations in humans—particularly for fungal microbiota—further investigation is needed.